Exploring Settlement Decisions in the Coastal Area: A Quantitative Study of Socio-Economic Factors in Bandar Lampung City - Husna Tiara Putri (Jurnal Perencanaan Wilayah dan Kota, 2025)
Coastal settlements continue to expand rapidly, driven by population growth and housing development shaped by diverse socio-economic and cultural factors. This study examines the factors influencing settlement decision in coastal areas through a quantitative approach, using questionnaires from 196 respondents and observations in eight sub-districts of Bandar Lampung. The city was selected due to its rapid coastal urbanization, with long-established yet continuously growing coastal settlements. The findings reveal that most residents—fishermen, traders, and laborers linked to urban and fisheries activities—have lived in these areas for over a decade. They primarily construct homes on coastal land and over water using wooden and brick structures. Economic factors, particularly affordable coastal land, are the most influential, alongside proximity to the city and family networks, which further drive continuous settlement growth. These trends underscore the urgent need for integrated spatial planning and stronger policy frameworks to balance urban expansion, environmental sustainability, and long-term coastal resilience.